2013
DOI: 10.1021/bc300594y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Enzymatic Site Specific PEGylation of hGH

Abstract: Several strategies for site-specific PEGylation have been successfully exploited to conjugate poly(ethylene glycol) (PEG) to pharmaceutical proteins. The advantages sought are those of improving efficacy and increasing the half-life of conjugated proteins while achieving a higher degree of homogeneity. Recombinant human growth hormone (hGH) was thus PEGylated exploiting two site-specific strategies: N-terminal PEGylation using the PEG20 kDa-aldehyde polymer and microbial transglutaminase (mTGase) mediated enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 32 publications
(55 reference statements)
3
50
0
Order By: Relevance
“…In vivo studies in rats demonstrated that both PEGylated products significantly improved systemic circulation and exerted a 4.5-fold increase in half-life relative to unmodified hGH. These results indicate that site-specific PEGylation of hGH helps to generate conjugates with prolonged half-life relative to native protein (hGH) [16]. …”
Section: Chemical Modificationsmentioning
confidence: 99%
“…In vivo studies in rats demonstrated that both PEGylated products significantly improved systemic circulation and exerted a 4.5-fold increase in half-life relative to unmodified hGH. These results indicate that site-specific PEGylation of hGH helps to generate conjugates with prolonged half-life relative to native protein (hGH) [16]. …”
Section: Chemical Modificationsmentioning
confidence: 99%
“…To circumvent this possibility, aldehyde groups have been introduced into the HA backbone by periodate oxidation, an approach widely exploited with polysaccharides containing vicinal hydroxyl groups. Mild reactive aldehydes can, in turn, make it possible to obtain a selective N-terminal protein conjugation, as has also been reported with regard to aldehyde-PEGs [71,72]. This strategy was used for the HAylation, for example, of interferon alpha and human growth hormone [73,74].…”
Section: Ha Conjugatesmentioning
confidence: 92%
“…For example, when TGase mediated PEGylation of hGH was compared to the well-know N-terminal PEGylation, the two approaches produced comparable results in terms of selectivity and preservation of protein secondary structures and the pharmacokinetic profiles of the mono-conjugates [72].…”
Section: Enzymatic Polymer Conjugationmentioning
confidence: 99%
“…In a recent publication, Browning et al showed 77 that acrylamide-PEG-isocyanate (AAm-PEG-I) linker can be incorporated onto proteins with PEG diacrylamide (PEGDAA) to enhance the hydrolytic stability and half-life of protein drugs. In another study da Silva Freitas et al 78 In one example, Lyon and coworkers 69,80 reported that loosely crosslinked microgels (composed of a random copolymer of N-isopropylacrylamide (NIPAm) and acrylic acid (AAc)) demonstrated a high loading capacity for protein. These kinds of microgels or microgel-based devices can be potentially used as protein drug delivery systems.…”
Section: Drug Deliverymentioning
confidence: 99%